The confraternities of Misericórdia and the Portuguese diasporas in the early modern period - Sá, Isabel dos Guimarães; Rodrigues, Lisbeth (European expansion and indigenous response, 2023)
"During the early modern period, the brotherhoods of Misericórdia were established not only in the overseas territories ruled by the Portuguese, but also beyond their empire, reaching as far as the Philippines and Japan. The twelve chapters of this book examine this expansion by discussing different dimensions of the Misericórdias, such as administration, politics, charitable practices, finances, and forms of discrimination related to social status, gender, and race. Filling a critical gap in anglophone scholarship on the Portuguese Misericórdias, this work's previous absence has been criticized by scholars who believe the Misericórdias are crucial to understanding the past and present of Portuguese communities, both at home and abroad"--